Outcomes of atrial fibrillation ablation in patients with or without silent pulmonary veins from prior ablation procedure. (15th June 2022) - Aguilera, Jose; Hutt, Erika; Kaur, Simrat; Saliba, Walid I.; Tarakji, Khaldoun G.; Baranowski, Bryan; Bhargava, Mandeep; Kanj, Mohamed; Cantillon, Daniel J.; Rickard, John; Sroubek, Jakub; Nakagawa, Hiroshi; et al.
Abstract: Introduction: Pulmonary venous (PV) electrical recovery underlies most arrhythmia recurrences after atrial fibrillation (AF) ablation. Little is known about procedural profiles and outcomes of patients with electrically silent PVs upon redo ablation for AF. Methods: In a prospectively maintained registry, we enrolled 838 consecutive patients (2013–2016) undergoing redo ablation procedures. Ablation procedures targeted the PVs, the PV antra, and non‐PV sites at operators' discretion. Procedural profiles and clinical outcomes were assessed. The primary outcome was freedom from AF after a 3‐month blanking period. The secondary outcome was improvement in quality of life. Results: Most patients undergoing redo AF ablation ( n = 684, 82%) had PV reconnection while the remaining 154 (18%) had electrically silent PVs. Patients with recurrent AF and electrically silent PVs were older (66 vs. 64 years, p = .02), had more prior ablation procedures (median 2 IQR 1–3 vs 1 IQR 1–2 p = .001), were more likely to have non‐paroxysmal AF (62% vs. 49%, p = .004) and atrial flutter (48% vs. 29%, p = .001) and had significantly larger left atrial volumes (89 vs. 81 ml, p = .003). Patients with silent PVs underwent a more extensive non‐PV ablation strategies with antral extension of prior ablation sets in addition to ablation of the roof, appendage, inferior to the right PVs, peri‐mitral flutter lines, cavotricuspid isthmus lines and ablation in the coronary sinus. Upon one year of follow‐up, patients with electrically silent PVs were less likely to remain free from recurrent atrial arrhythmias (64% vs. 76%, p = .008). Regardless of PV reconnection status, redo ablation resulted in improvement in quality of life. Conclusion: Rhythm control with extensive ablation allowed maintenance of sinus rhythm in about two thirds of patients with silent PVs during redo AF ablation procedures. Regardless of PV reconnection status, redo ablation resulted in improvement in quality of life. This remains a challenging group of patients, highlighting the need to better understand non‐PV mediated AF.